The perception of Covid-19 amongst vulnerable subgroups of the general population in Italy: insights from the qualitative study of the MOST project - Francesco Iocca; Barbara Giangrasso; Giulia Fioravanti; Daniele Pugi; Nicole Loren Angelo; David Baldo; Andrea Failli; Valerio Vignoli; Ada Fort; Giovanna Millozzi; Giacomo Gualtieri; Lore Lorenzi; et al. (BMC Psychology)
Abstract Background The Covid-19 pandemic has had significant consequences on the well-being of individuals worldwide. However, some subgroups may be more affected, presenting numerous distressing psychological symptoms such as depression, anxiety and stress. The present study aims to explore the needs and concerns of the most vulnerable populations during the pandemic. Methods Online focus groups were conducted with representatives of five vulnerable populations: frontline and non-frontline healthcare workers, young adults, older people, and entrepreneurs. The interviews with each group were transcribed, and an inducted theme analysis, based on the Health Belief Model, was conducted to identify recurring themes and build and implement a tailored intervention. Results Qualitative differences between groups emerged in risk perception, one of the main domains of the Health Belief Model, while similarities emerged in the perceived cost of the pandemic. Other themes that emerged included vaccination intention, future expectations, protective measures usage, and information searching. Conclusions The findings of the present study may help shape a Health Belief Model-based intervention to promote well-being and the use of protective measures during pandemics.